Intracystic Hemorrhage Complicating Polycystic Liver Disease in a 90-Year-Old Woman - Purdy, Amanda C. (ACG Case Rep J, 2019)
Nonparasitic hepatic cysts are common benign tumors that are often asymptomatic and incidentally discovered on imaging. Intracystic hemorrhage is a rare complication of hepatic cysts. We review the literature and discuss a case of intracystic hemorrhage in a 90-year-old woman with polycystic liver disease. The patient underwent cyst aspiration and percutaneous drain placement with subsequent resolution of symptoms. To our knowledge, we report the oldest patient to present with hemorrhage into a hepatic cyst. This case presents unique challenges in management, both because of the patient's age and because of her polycystic liver disease.